Psychopragmatics in Social Media: An Analysis of Pragmatic Cues in Online Communication (International Forum of Researchers and Lecturers, 2024)
This article explores how social media users leverage pragmatic cues, such as emojis, hashtags, and other forms of non-verbal communication, to convey emotional and contextual nuances in online interactions. The study aims to understand the role of these elements in shaping meaning and enriching communication on digital platforms. This study employed a qualitative research approach, utilizing content analysis as the primary method for data collection and analysis. By analyzing various social media posts and comments, the research highlights the significance of pragmatic cues in enhancing user engagement and facilitating a deeper understanding of messages. The research emphasizes the significant impact of emojis and hashtags on communication in social media. A large majority of users use emojis to express emotions, which can boost engagement by up to 30%. Emojis add emotional depth, with 75% of respondents viewing messages with a (worried) emoji as more serious and 80% finding those with a (smile) emoji funnier. Hashtags enhance visibility and interaction, as 65% of tweets with hashtags receive retweets compared to only 30% without them. Context is crucial, with 80% of posts related to social movements receiving positive comments when paired with relevant hashtags. The use of GIFs and emojis also increases user engagement, with GIFs achieving a 40% higher interaction rate than text-only posts. However, messages lacking these non-verbal elements often lead to misunderstandings, with 70% of conversations experiencing confusion without them. The study highlights cultural differences in emoji interpretation, indicating that meanings can vary significantly across cultures.